Integrated Three-Level Supply Chain Model for Optimality of Inventory and Shipment Decisions under Cubic Price Dependent Demand. (2018) - Nagaraju, Dega; Narayanan, S.; Manupati, V.K.; Ramakrishna Rao, A.
Abstract: In this paper, a three-level supply chain with a single-manufacturer supplying a single kind of product to a single-distributor and then to a single-retailer is considered. Mathematical model is developed for optimal net revenue of the coordinated three-level supply chain by incorporating ordering cost, carrying cost and transportation cost. In the proposed model, the demand at the retailer is assumed as a cubic function of unit selling price. The objective of this work is to demonstrate the optimality of decision variables, i.e., inventory decisions and shipment policies for the respective entities under cubic price dependent demand. Also, it is aimed at demonstrating the optimal net revenue of the individual entities as well as the entire chain. For the purpose of numerical illustration, a computer program is written in MATLAB and the model is solved to determine the optimal values of decision variables and objective function. Also, sensitivity analysis is carried out and few managerial implications are derived.